Moral Distress: Recognition, Diagnosis, and Treatment. Issue 4 (July 2015) - Trautmann, Jennifer
Abstract : Infusion nursing is a unique hybrid of inpatient and ambulatory nursing. The subspecialty of nurses cares for patients requiring treatment over long periods, including cancer patients receiving chemotherapy and patients who require short bursts of treatment, such as those with multiple sclerosis, Crohn's disease, and rheumatoid arthritis. Infusion nurses are exposed to many of the common root causes of moral distress in their practice, similar to nurses caring for terminally ill or critically ill patients. The specific aims of this article are to (1) define moral distress, moral residue, and the crescendo effect; (2) describe ethical stressors that can be confused with moral distress; (3) review the effects of moral distress on different health care providers; and (4) provide strategies to manage moral distress in the workplace using a case example.